EVALUATION OF PHYSICAL STABILITY OF BOESENBERGIA ROTUNDA EXTRACT FORMULATED IN NANOEMULGEL - Pratiwi, Rosa; Sari, Rina Kartika; Amanda, Shania Dwika (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Pinostrobin compounds from extracts of Boesenbergia rotunda have broad spectrum for bacteriostatic activity. The nanoemulgel preparation was chosen because it can penetrate well and quickly into the mucosa thereby increasing absorption. Physical stability tests need to be carried out to ensure the quality, safety and benefits of the gel meet the expected specifications and stability during storage. This study aims to determine which concentration has the most stable physical stability of pH and viscosity which were observed for 28 days.Method: 30 samples nanoemulgel preparation was used and then divided into 3 groups 45%, 67.5%, and 90%, Physical stability tests which is pH and viscosity tests was done for 28 days and stored in the Climatic Chamber with observation for every seven days. Data analysis used the One Way Repeated Measure Anova test followed by post hoc test was carried out. Result: The results showed most stable preparation was 45% and the least stable was 90% concentration. The mean values of the pH test 45% and 90% at baseline were 4.43 and 4.46 and at H+28 the values were 4.49 and 4.56. The average value of the viscosity test 45% and 90% at baseline was 1550 and 1210 and the values were 1600 and 1240 at h+28. Post hoc Wilcoxon test results for 45% concentration were p>0.05, indicating that there was no difference in pH and viscosity. It means pH value and viscosity of the 45% concentration were relatively constant from baseline to H+28.Conclusion: In conclusion, the results pH test and viscosity test of nanoemulgel preparations that were observed for 28 days showed that most stable preparation was concentration of 45%.